Randomized, Double-masked, Placebo-controlled Clinical Trial on the Effects of Propolis and Chlorhexidine Mouthrinses on Gingivitis - Camilo Anauate-Netto; Andréa Anido-Anido; Hugo Roberto Lewgoy; Ricardo Matsumoto; Roberta Caroline Bruschi Alonso; Maria Cristina Marcucci; Niraldo Paulino; Walter Antonio Bretz (Brazilian Dental Science)
Objective: The aim of this study was to compare the effects of typified propolis and chlorhexidine mouthrinses on gingival health in a randomized double-masked placebo-controlled clinical trial.